Modelling arm coordination in front crawl - Seifert, L.; Chollet, D. (Biomechanics and Medicine in Swimming XI, 2010)
Regularly, arm coordination of front crawl swimmers switched from catch-up to superposition mode when speed was found to increase. The aim of this study was to model the relationships between the index of coordination (IdC) and speed (V). Twenty male swimmers of various skill level and specialty (sprint vs. distance) realised an incremental speed test of 8 × 25-m steps. After checking the change of arm coordination with speed, 5 models of regression were tested: power, logarithmic, exponential, linear and quadratic. The model was done by averaging the individual coefficient; then percent of error with the model was determined for each swimmer. The quadratic modelling (IdC =aV²+bV+c) showed the highest coefficient of determination (0.81<R²<0.99) and the lower inter-individual mean error with the model (21%). Arm coordination modelling enabled to relate motor control with the performance (V), the stroking parameters (stroke rate and stroke length) and the stroke efficiency (stroke index).